Transparent wafer-scale self-standing fluorinated graphene films. (15th January 2023) - Colin, Marie; Chen, Sam; Farhat, Hani; Guérin, Katia; Dubois, Marc
Abstract: The fluorination of self-standing graphene oxide (GO) films under mild conditions at 70 °C for 1h using a mixture of elemental fluorine and nitrogen gases (0.35 F2 /0.65 N2 v/v) results in transparent, highly fluorinated (F/C = 1 as seen by XPS) graphene oxide (FGO) films which maintain initial densely packed structure and mechanical strength. Most of the oxygen atoms in the GO film were replaced by fluorine after fluorination, and two types of carbon-fluorine bonds coexist, i.e. primarily weakened C⋯F bonds and also pure covalent C–F bonds as evidenced by FTIR, XPS, NMR, and cyclic voltammetry when FGO is used as electrode in Li/electrolyte (PC:EC:3DMC/LiTFSI 1 M)/FGO cell similar to a lithium battery. To further understand the fluorination mechanism and to distinguish the reaction steps, xenon difluoride XeF2 was used as fluorinating agent for GO and in situ EPR and FTIR analyses suggest hydroxyl groups as preferential reactive sites. These self-standing transparent FGO films exhibit unusual electrochemical properties in lithium battery and can be used as hydrophobic lubricant membranes because of the low and stable coefficient of friction evidenced in the present work. Graphical abstract: Image 1